The Effects of Family Function, Nurse-Patient Communication, and Stigma on Depression Symptoms in Tuberculosis Patients at the DOTS Pulmonary Outpatient Clinic of RSUD Banyumas - Febri Restu Ristiyanti; Supriyadi Supriyadi (Proceedings Series on Health & Medical Sciences, 2024)
Background: Tuberculosis (TB) and mental illness are prevalent worldwide and often coexist. Poor mental health has been linked to alterations in immune function. Through social, behavioral, and biological mechanisms, depression and tuberculosis together amplify the burden of disease. Collaboration from all parties is needed to alleviate depression in TB patients, including support from family function and positive societal stigma. Method: This was a descriptive correlational study, and data collection was carried out using a cross-sectional method. A total of 72 respondents who met the inclusion and exclusion criteria were selected as the sample using a non-probability sampling technique, specifically accidental sampling. Results: The results of the multiple regression test showed that only the variables of family function and stigma had a significant correlation with p-values of 0.00005 and 0.009 0.05, respectively. Meanwhile, the variable of nurse-patient communication had a p-value of 0.633 0.05, indicating no significant correlation. Additionally, the calculated F-value was 18.662, and the tabled F-value was 3.136, with a probability value of 0.000. Since the probability value was less than 0.05, the regression model could be used to predict depression symptoms. It can be stated that the three independent variables, namely family function, nurse-patient communication, and stigma, collectively influence depression symptoms in patients. Conclusion: There is a significant relationship between family function and stigma towards depression symptoms in Tuberculosis patients at the DOTS Pulmonary Clinic of Banyumas Regional Public Hospital in 2023.